Temporal and angular variations of 3D core-collapse supernova emissions and their physical correlations. Issue 2 (21st August 2019) - Vartanyan, David; Burrows, Adam; Radice, David
Abstract: We provide the time series and angular distributions of the neutrino and gravitational wave emissions of 11 state-of-the-art 3D non-rotating core-collapse supernova models and explore correlations between these signatures and the real-time dynamics of the shock and the proto-neutron star (PNS) core. The neutrino emissions are roughly isotropic on average, with instantaneous excursions about the mean inferred luminosity of as much as ±20 per cent. The deviation from isotropy is least for the 'νμ '-type neutrinos and the lowest mass progenitors. Instantaneous temporal luminosity variations along a given direction for exploding models average ∼2–4 per cent, but can be as high as ∼10 per cent. For non-exploding models, they can achieve ∼25 per cent. The temporal variations in the neutrino emissions correlate with the temporal and angular variations in the mass accretion rate. We witness the lepton-number emission self-sustained asymmetry (LESA) phenomenon in all our models and find that the vector direction of the LESA dipole and that of the inner Y e distribution are highly correlated. For our entire set of 3D models, we find strong connections between the cumulative neutrino energy losses, the radius of the proto-neutron star, and the f-mode frequency of the gravitational wave emissions. When physically normalized, the progenitor-to-progenitor variation in any of these quantities is no more than ∼10 per cent. Moreover, the reduced f-mode frequency is independent of time after bounce to better than ∼10 per cent. Therefore, simultaneous measurement of gravitational waves and neutrinos from a given supernova event can be used synergistically to extract real physical quantities of the supernova core.